Exposure to smoking on patios and quitting: a population representative longitudinal cohort study. Issue 1 (28th October 2014) - Chaiton, Michael; Diemert, Lori; Zhang, Bo; Kennedy, Ryan D; Cohen, Joanna E; Bondy, Susan J; Ferrence, Roberta
Abstract : Objectives: Smoke-free policies not only reduce harm to non-smokers, they may also reduce harm to smokers by decreasing the number of cigarettes smoked and increasing the likelihood of a successful quit attempt. However, little is known about the impact of exposure to smoking on patios on smoking behaviour. Design and participants: Smokers from the Ontario Tobacco Survey, a longitudinal population representative cohort of smokers (2005–2011). There were 3460 current smokers who had completed one to six follow-ups and were asked at each follow-up whether or not they had been exposed to smoking on patios in the month. Main outcome measures: Generalised estimating equations and survival analysis were used to examine the association between exposure to patio smoking and smoking behaviour changes (making a quit attempt and time to relapse after a quit attempt), controlling for potential confounders. Results: Smokers who were exposed to smoking on patios (adjusted incident rate ratio (aIRR) = 0.89; 95% CI 0.81 to 0.97) or had been to a patio (aIRR = 0.86; 95% CI 0.74 to 0.99) were less likely to have made a quit attempt than smokers who had not visited a patio. Smokers who were exposed to smoking on patios were more likely to relapse (adjusted HR=2.40; 95% CI 1.07 to 5.40)) after making a quit attempt than those who visited a patio but were not exposed to smoking. Conclusions: Exposure to smoking on patios of a bar or restaurant is associated with a lower likelihood of success in a quit attempt. Instituting smoke-free patio regulations may help smokers avoid relapse after quitting.